STUDENTS AND TEACHERS’ PERCEPTIONS CONCERNING SMARTPHONE USAGE IN EFL LEARNING - Pale, Erlinda Sonya; Luruk, Fransiska Densiana; Seran, Primus; Leda Leu, Aloysia Trivonia (Premise: Journal of English Education and Applied Linguistics, 2023)
The infancy of research on junior high school students and English teachers in the border areas concerning the implementation of smartphones in English learning triggered the researchers to conduct a study to deal with the phenomenon. Hence, a recent study was undertaken to acquire the following goals. 1) to identify the level of smartphone utilization as a medium of learning English at SMP Satap Sono and SMPN Napan. 2) to know the perception of the students and English teachers of SMP Satap Sono and SMPN Napan towards using smartphones as a medium for learning English. This study embraced 60 participants comprising 30 students from SMPN Napan and 30 from SMPN Sono, as well as 3 English teachers from the two schools. The research design applied was qualitative descriptive. To procure data, the researchers applied three instruments: questionnaires, interviews, and class observation. The researchers observed the learning process in which English teachers and students incorporated smartphones, distributed questionnaires to the students and the English teachers, and interviewed the students and the English teachers concerning the implementation of smartphones as a medium in English learning. Further, the data were scrutinized by a descriptive method. Research results signified that the level of using the smartphone in learning English for the students and English teachers in SMP Satap Sono and SMPN Napan was categorized as low. On the contrary, the English teachers and the students had positive perceptions of the application of smartphones to support English learning. Then, the current study could inform the English teachers at the two schools on how their students perceive the integration of smartphones. Henceforth, it is expected that the subsequent researchers could explore a variety of English learning applications to be applied by the students and teachers at the border area.